Current Population Survey, September 2013: Volunteer Supplement ([Verlag nicht ermittelbar], 2015)
This data collection is comprised of responses from two sets of survey questionnaires, the basic Current Population Survey (CPS) and a survey on the topic of volunteer service, which was administered as a supplement to the September CPS questionnaire. The Corporation for National and Community Service jointly sponsored the supplemental questions for September. The CPS, administered monthly, is a labor force survey providing current estimates of the economic status and activities of the population of the United States. Specifically, the CPS provides estimates of total employment (both farm and nonfarm), nonfarm self-employed persons, domestics, and unpaid helpers in nonfarm family enterprises, wage and salaried employees, and estimates of total unemployment. Data from the CPS are provided for the week prior to the survey. All persons eligible for the labor force items of the basic CPS were also eligible for the volunteer supplement. Altogether, 149,961 interviews were conducted during the period of September 15-24, 2013. Proxy responses were allowed if attempts for a self-response were unsuccessful. The supplement contained questions about the household member's participation in volunteer service from September 1, 2012, to the date of the interview. Household members were queried about the frequency of volunteer activity, the kinds of organizations they volunteered with, the types of activities they chose, whether any volunteering was done in a foreign country, and involvement in their community. Demographic variables include age, sex, race, Hispanic origin, marital status, veteran status, educational attainment, occupation, and income.